Estructura y diversidad florística del bosque los pijíos en el Cantón isidro ayora Provincia del Guayas, en el 2013. - Carrera Díaz, Carlos Gabriel (2014)
It realized a study of the structure of the vegetation of a tropical dry forest in the Isidro Ayora canton, Guayas province; the site is located at UTM coordinates 9770954 East and 595820 South, at an altitude of 120 meters. Were established 16 sampling units stratified of 400 m2, were taken common name, DAP, total and commercial height and cup diameter of the trees and shrubs present in the UM. It was determined the Shannon -Wiener diversity Index, Importance value, forest value index, relative sociological position and natural regeneration. 1499 trees and shrubs were recorded in different structural floors of the forest, which belong to 66 species, of which 9 species are unknown, 64 genera and 35 families, of which 3 are unknown. The most representative families of the forest "Los Pijíos" are: FABACEAE, BOMBACACEAE, EUPHORBIACEAE, MORACEAE and BIGNONIACEAE. The forest is made up of a lot of young vegetation with few mature trees where diameter class classification shows an shape of inverted J. The species with the highest IVI % in the upper stratum is Cavanillesia platanifolia (Bonpl.) Kunth. (pijio) in the middle stratum is Simira standleyi (Little) Steyerm . (colorado). The species with the highest IVF % in the upper stratum and the stratum medium is Simira standleyi (Little) Steyerm . (colorado) . It was determined that the species with more PSr % were Cynometra bauhinifolia Benth. (cocobolo) and Simira standleyi (Little) Steyerm. (colorado) . with respect to natural regeneration, the Cynometra bauhinifolia Benth. (cocobolo), has an important 3 times the Simira standleyi (Little) Steyerm (colorado).